2013
DOI: 10.1155/2013/593020
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of NF-κB by Dehydroxymethylepoxyquinomicin Suppresses Invasion and Synergistically Potentiates Temozolomide and γ-Radiation Cytotoxicity in Glioblastoma Cells

Abstract: Despite advances in neurosurgery and aggressive treatment with temozolomide (TMZ) and radiation, the overall survival of patients with glioblastoma (GBM) remains poor. Vast evidence has indicated that the nuclear factor NF-κB is constitutively activated in cancer cells, playing key roles in growth and survival. Recently, Dehydroxymethylepoxyquinomicin (DHMEQ) has shown to be a selective NF-κB inhibitor with antiproliferative properties in GBM. In the present study, the ability of DHMEQ to surmount tumor's inva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 63 publications
3
20
0
Order By: Relevance
“…Proneural-mesenchymal transition (PMT) has been identified as a process of cancer progression and is related to the mechanism for TMZ resistance in GBM [20]. The induction of PMT post-radiation therapy through the activation of the NF-κB and STAT3 pathways by inflammatory agents, such as IL-6, TNF-α, etc., has been found in GBM [32][33][34]. Moreover, IL-6 overexpression has been identified as a marker of malignancy in GBM [35].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Proneural-mesenchymal transition (PMT) has been identified as a process of cancer progression and is related to the mechanism for TMZ resistance in GBM [20]. The induction of PMT post-radiation therapy through the activation of the NF-κB and STAT3 pathways by inflammatory agents, such as IL-6, TNF-α, etc., has been found in GBM [32][33][34]. Moreover, IL-6 overexpression has been identified as a marker of malignancy in GBM [35].…”
Section: Discussionmentioning
confidence: 98%
“…The overexpression of ectopic p65 or high constitutive NF-κB activity has been shown to elevate MGMT and thereby enhance chemoresistance to alkylating agents in detected cells [37]. In contrast, the inhibition of NF-κB by the small molecule inhibitor BAY 11-7082 or by siRNA-mediated gene silencing reduced MGMT levels and thereby sensitized glioma stem-like cells to TMZ treatment [30,32]. Here, we found that H2AFJ expression causally modulates the activity of NF-κB in GBM cells.…”
Section: Discussionmentioning
confidence: 99%
“…Several therapeutic inhibitors which can block NF-κB activation are in development. Dehydroxymethylepoxyquinomicin (DHMEQ) has been reported to be an effective NF-κB inhibitor with antiproliferative properties in GBM (40). Triptolide was able to inhibit NF-κB signaling in glioma initiating cells, and then synergistically enhances TMZ-induced apoptosis (41).…”
Section: Discussionmentioning
confidence: 99%
“…Preclinical testing of DHMEQ demonstrated inhibition of NF-κB activation and nuclear translocation, which led to decreased proliferation in GBM cells in vitro and decreased tumor growth in vivo . DHMEQ treatment also synergizes with TMZ and radiation, indicating strong therapeutic potential [69]. Recently, we published in vivo data demonstrating Withaferin A (WA), an IKKβ inhibitor, showed promise at inhibiting NF-κB and GBM growth [70].…”
Section: Nf-κb Signaling In Glioma: Preclinical Datamentioning
confidence: 99%